The introduction of video games in the museum content: De la intención al diseño de experiencias - Mihura López, Rocío; Seoane Nolasco, Antonio; Piñeiro Otero, Teresa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In recent decades there has been a radical change in the concept of the museum towards the valorization of the experience as a way of acquiring knowledge. This change has generated an environment conducive to the entry of interactive digital installations that combine information and education with a playful perspective that often leads them to transfer elements and features of video games for a more attractive, immersive and memorable experience. The purpose of this article has been to redefine elements of video game design and its intersection with user-centered design for its application in the museum context.